2014
DOI: 10.1007/s00213-014-3721-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled vs. oral alprazolam: subjective, behavioral and cognitive effects, and modestly increased abuse potential

Abstract: Rationale Infrahuman and human studies suggest that a determinant of the abuse potential of a drug is rate of onset of subjective effects. Objectives This study sought to determine if the rate of onset of subjective effects and abuse potential of alprazolam would be increased when administered via inhalation vs. the oral route. Methods Placebo, inhaled alprazolam (0.5, 1, 2 mg), and oral alprazolam (1, 2, 4 mg) were administered under double-blind, double-dummy conditions using a cross-over design in 14 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…However, nicotine gum yielded higher overall nicotine uptake than even the highest nicotine content Vuse Solo EC. Taken together, the findings in this study extend earlier findings with nicotine and other dependence-producing substances that the abuse liability of a given substance can be strongly influenced by the form or formulation and route of administration and is generally related to the speed of absorption of the substance (FDA 2010 , 2015 , 2017 ; Calderon and Klein 2014 ; Fant et al 1999 ; Fant et al 1997 ; Grudzinskas et al 2006 ; Henningfield and Keenan 1993 ; Reissig et al 2015 ).…”
Section: Discussionsupporting
confidence: 83%
“…However, nicotine gum yielded higher overall nicotine uptake than even the highest nicotine content Vuse Solo EC. Taken together, the findings in this study extend earlier findings with nicotine and other dependence-producing substances that the abuse liability of a given substance can be strongly influenced by the form or formulation and route of administration and is generally related to the speed of absorption of the substance (FDA 2010 , 2015 , 2017 ; Calderon and Klein 2014 ; Fant et al 1999 ; Fant et al 1997 ; Grudzinskas et al 2006 ; Henningfield and Keenan 1993 ; Reissig et al 2015 ).…”
Section: Discussionsupporting
confidence: 83%
“…Singh, Jain, Ray, and Gupta 2001demonstrated that intravenous diazepam had a higher abuse liability than oral diazepam as it produced more rapid and greater positive subjective effects. However, Reissig, Harrison, Carter, and Griffiths (2015) showed that inhaled alprazolam only modestly increased positive subjective effects compared with those effects produced by oral alprazolam even though the time of the onset of effects was much more rapid in the former route. These results indicate that although typically some routes are associated with faster absorption and faster onset of effects, there are other factors that influence the magnitude of the subjective effects when comparing routes i.e.…”
Section: The Role Of Pharmacokinetics and Routes Of Administration Inmentioning
confidence: 94%
“…And at least one study reported that increased caffeine consumption is linked with increased risk-taking in adolescents ( Temple et al, 2017b ). Finally, prescription stimulant medications have been linked with cognitive enhancement ( Bagot and Kaminer, 2014 ; Coghill et al, 2014 ; Tamminga et al, 2016 ), while prescription anxiolytics/sedatives ( Meador et al, 2011 ; Loring et al, 2012 ; Reissig et al, 2015 ; Ghoneim et al, 1984 ) and opiates ( Allen et al, 2003 ; Schoedel et al, 2010 ) negatively impact memory, processing speed and attention. Over the counter (OTC) cough medication containing dextromethorphan has been linked with cortical thickness in adolescents in one study ( Qiu et al, 2016 ), although this outcome has yet been replicated.…”
Section: Background and Rationalementioning
confidence: 99%